Two-parameter Envelope Calculation for the Profile of Worm Grinding Wheel and Dressing Method - Shuai Wang; Bin Li; Jianjun Yang; Laigui Lei; Jinwei Zhao; Jianxin Su (Jixie chuandong)
A mathematical model for tooth profile curve of cylinder gear with high-order modification gear surface is established. Applying two-parameter envelope theory to determine the meshing relationship between worm grinding wheel and helical gears，the transverse tooth profile is calculated. The grinding wheel dressing and gear grinding experiments are conducted on worm grinding wheel gear grinding machine. According to the results of tooth profile deviation measurement，the tooth surface modification curve is coincided with the requirements. The experiment results verify the correctness of calculation and effectiveness of dressing for worm grinding wheel profile curve.